2017
DOI: 10.3389/fphys.2017.00444
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 6-Weeks High-Intensity Interval Training in Schoolchildren with Insulin Resistance: Influence of Biological Maturation on Metabolic, Body Composition, Cardiovascular and Performance Non-responses

Abstract: Background: Previous studies have observed significant heterogeneity in the magnitude of change in measures of metabolic response to exercise training. There are a lack of studies examining the prevalence of non-responders (NRs) in children while considering other potential environmental factors involved such as biological maturation.Aim: To compare the effects and prevalence of NRs to improve the insulin resistance level (by HOMA-IR), as well as to other anthropometric, cardiovascular, and performance co-vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 42 publications
2
57
0
3
Order By: Relevance
“…Aunque factores genéticos 13 , y ambientales [14][15][16] han sido escuetamente explorados, aún no se identifican los potenciales factores ambientales que dan cuenta de este fenómeno. Descartando la influencia genética que varía individualmente, no está del todo claro qué parámetros de salud, por ejemplo, composición corporal, presión arterial o marcadores metabólicos como los triglicéridos, presentan mayor o menor prevalencia de sujetos no respondedores en la población adherente a ejercicio.…”
unclassified
“…Aunque factores genéticos 13 , y ambientales [14][15][16] han sido escuetamente explorados, aún no se identifican los potenciales factores ambientales que dan cuenta de este fenómeno. Descartando la influencia genética que varía individualmente, no está del todo claro qué parámetros de salud, por ejemplo, composición corporal, presión arterial o marcadores metabólicos como los triglicéridos, presentan mayor o menor prevalencia de sujetos no respondedores en la población adherente a ejercicio.…”
unclassified
“…After a 6-week exercise training programme in schoolchildren engaging HIT (three sessions/week) Alvarez et al reported a decrease of~22% in both FINS and HOMA-IR in children with IR, and also a prevalence of NRs of~80-90% for decreasing FGL, 30-40% for decreasing FINS and~25-35% for decreasing HOMA-IR in children tested by biological maturation (19). In the present study, it can be seen that individuals who were Rs in one outcome would not necessarily be Rs in another outcome (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…After the intervention, the delta changes were calculated for each dependent outcome. Consequently, the subjects were categorized as Rs or NRs according to previously described criteria of 2 × TE for the glucose control outcomes (fasting glucose 2 × TE; 3.0 mg/dL, 2 × TE; fasting insulin 2.18 μIU/dL, 2 × TE; HOMA‐IR 0.42) . The odds ratios (ORs) were used to assess the risk for suffering NRs between groups.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, some individuals show improvements with exercise training (eg, decrease in fasting glucose) and are considered responders , whereas others may not have such a response (eg, no change or even increases in fasting glucose) and are considered non‐responders . Individual variability has been reported mainly regarding fitness‐related variables, and in response to moderate‐intensity endurance (ET), resistance (RT), or high‐intensity interval training (HIT), and also in different age groups such as children, adults, or older populations, The existence of non‐responders for glucose homeostasis‐related variables has been confirmed more recently . In the present study, we confirmed a wide interindividual variability that is independent of the training‐induced changes after HIT, RT, or CT with regard to 20 outcomes and risk parameters, including 9 body composition, 3 cardiovascular, 3 metabolic, and 5 performance parameters.…”
Section: Perspectivesmentioning
confidence: 99%
“…3 For instance, some individuals show improvements with exercise training (eg, decrease in fasting glucose) and are considered responders, whereas others may not have such a response (eg, no change or even increases in fasting glucose) and are considered non-responders. 4 The interindividual variability has been reported mainly in the context of fitness-related variables, 5 and in response to moderate-intensity endurance (ET), 3,6 resistance (RT), 7 or high-intensity interval training (HIT), 7 and also in different age groups such as children, 8 adults, 9,10 or older populations. 7,11 The existence of non-responders for glucose homeostasis-related variables has been confirmed more recently.…”
Section: Introductionmentioning
confidence: 99%